Uso de auxinas y citoquininas en componentes productivos del cacao (Theobroma cacao L.) ccn-51 asociado con balsa (Ochroma pyramidale), Mocache 2022 - Taipe Buste, Meyber Yeanell (2022)
Agroforestry systems associated with crops of economic interest stand out for their benefits, among which is the gain of organic matter in the soil, which gives rise to a greater diversity of organisms, decomposers that facilitate mineralization and therefore the availability of nutrients. in the soil, which is reflected in the development of the plants, however, due to the scarce quantitative information on the subject, the farmer is limited to planting in monoculture, with this background the present investigation was developed, which was located in the Lechugal enclosure, in the "El Ensueño" farm belonging to the Association of Lechugal Producers, Mocache canton, which aimed to evaluate the vegetative and reproductive behavior of cocoa